2006
DOI: 10.1243/13506501jet162
|View full text |Cite
|
Sign up to set email alerts
|

Simulated fuel dilution and friction-modifier effects on piston ring friction

Abstract: Government legislation, customer requirement, and pressure from the original equipment manufacturers (OEM) continually pushes the issue of increased vehicle fuel economy to the forefront. Lubricant manufacturers responded by creating low viscosity lubricants with complex additive packages capable of reducing total engine friction while maintaining the useful life of the engine. An important component in the lubricant additive package is the friction modifier, whose job is to reduce the sliding friction of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…4 shows the coefficient of friction of the stearic acid dispersed oil to decrease with time initially (up to 400 s) and then to stabilized to a time invariant value of 0.09. The recorded value of coefficient of friction matches well with those reported in literature [11]. The coefficient of friction corresponding to the linoleic acid dispersed in oil decreases steadily with sliding time till (4000 s) it appears to reach a steady average value of about 0.04.…”
Section: Lubricated Tribologysupporting
confidence: 89%
See 2 more Smart Citations
“…4 shows the coefficient of friction of the stearic acid dispersed oil to decrease with time initially (up to 400 s) and then to stabilized to a time invariant value of 0.09. The recorded value of coefficient of friction matches well with those reported in literature [11]. The coefficient of friction corresponding to the linoleic acid dispersed in oil decreases steadily with sliding time till (4000 s) it appears to reach a steady average value of about 0.04.…”
Section: Lubricated Tribologysupporting
confidence: 89%
“…Adhvaryu et al [19] based on their study of multicomponent biobased lubricants also observed that increasing unsaturation lowers the ability of the molecules to be chemisorbed. The work of Smith et al [11] using a reciprocating tribometer however showed that the effect of unsaturation at low loads and temperatures is marginal while at higher loads and temperatures unsaturation reduces friction substantially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, approximately 30 % reduction of kinetic friction was achieved by the addition of PA ( Figure S3). These additive effects for macroscopic rough surfaces are compatible with previous studies [8,9,[40][41][42] and are very different from our SFA results. We believe this is reasonable mainly because of the following reason.…”
Section: Comparison With Macroscopic Friction/stiction Behaviorssupporting
confidence: 62%
“…It can record instantaneous friction force and electrical contact potential, with the limits 0 and 50 mV indicating metal-on-metal contact and complete contact separation, respectively, based on the well established contact potential method of Furey [19]. This TE77 had been previously modified [20] so that lubrication can be provided from one of two sumps which can be switched during testing as shown in Fig. 1.…”
Section: Tribometermentioning
confidence: 99%